Contextual Issues Surrounding Investigative Journalism in Nigeria - Eric Msughter Aondover; Perpetua Ogechi Aondover; Olugbenga Charles Adewale; Funmi Falobi; Abdullahi Aliyu Maiwada (Britain International for Academic Research (BIAR-Publisher), 2024)
Investigative journalism in Nigeria faces numerous contextual issues that influence its effectiveness and the quality of reporting. These challenges can be categorized into political, economic, social, and professional dimensions. Investigative journalists often face intimidation, harassment, and arbitrary arrests by government authorities. Nigeria's laws, such as the Cybercrime Act, are sometimes used to suppress critical reporting. Despite constitutional guarantees, press freedom is often undermined by restrictive regulations and informal pressures. Investigative journalists working on issues related to corruption, terrorism, or organized crime may face direct threats to their safety. The rise of terrorist groups like Boko Haram in the north and violent criminal groups like bandits has made certain regions particularly dangerous for journalists. Attacks on journalists, kidnappings, and assassinations have become increasingly common, with little accountability for perpetrators. Journalism in Nigeria often faces financial constraints, which limit investigative reporting. Media outlets are frequently underfunded, and journalists may lack the resources to conduct thorough investigations, travel to relevant locations, or access key information. Moreover, media owners may have their own political or economic interests, which may affect editorial independence and discourage deep investigative work. The paper also argues that many media organizations are owned by political elites or business moguls, which can lead to biased reporting and self-censorship to protect the owners' interests. Similarly, journalists working online are vulnerable to hacking, surveillance, and digital harassment.